2022
DOI: 10.3390/ijerph191610349
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Traffic Signs Information Volume Affecting Driver’s Visual Characteristics and Driving Safety

Abstract: To study the influence of traffic signs information volume (TSIV) on drivers’ visual characteristics and driving safety, the simulation scenarios of different levels of TSIV were established, and 30 participants were recruited for simulated driving tests. The eye tracker was used to collect eye movement data under three-speed conditions (60 km/h, 80 km/h, and 100 km/h) and different levels of TSIV (0 bits/km, 10 bits/km, 20 bits/km, 30 bits/km, 40 bits/km, and 50 bits/km). Principal component analysis (PCA) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
(47 reference statements)
2
6
0
Order By: Relevance
“…The analytic hierarchy process was used to determine the importance of different information elements included in traffic signs in accordance with the drivers’ own individual assessments of their significance. The present study also adopts the same method to finally determine the weight of seven types of information elements in traffic signs ( 23 ). Table 1 displays the information volume and weight of each information element.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analytic hierarchy process was used to determine the importance of different information elements included in traffic signs in accordance with the drivers’ own individual assessments of their significance. The present study also adopts the same method to finally determine the weight of seven types of information elements in traffic signs ( 23 ). Table 1 displays the information volume and weight of each information element.…”
Section: Methodsmentioning
confidence: 99%
“…When the TSIV was more than 642 bits, there was an excess of information. To assure the driver’s safety and comfort, Han et al ( 23 ) examined the participant’s visual characteristics at varying driving speeds and TSIV levels, and found that the driver’s fixation duration, saccade duration, and saccade amplitude were most responsive to the change in TSIV. Using simulated driving tests and questionnaires, Xu et al ( 50 ) assessed the information threshold of graphical VMS and discovered that the number of roads displayed on the VMS negatively affected drivers’ legibility speed, legibility time, and subjective scores, with a significant drop in accuracy when the VMS displayed six road numbers.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…From the perspective of human factors, the increase in the volume of sign information does not affect the cognitive ability of drivers due to their age [27] . The most crucial human factor in improving driver cognitive ability is the driver's driving experience [29] . Meanwhile, as the level of information increases, gender will begin to affect drivers' cognitive abilities [30] .…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Especially the driving pattern of two-wheeled vehicles is stochastic in the absence of lane discipline or turning motion discipline at intersections in traffic conditions, which affects the safety and overall characteristics of traffic flow. Arbitrary placement of traffic signs is becoming more common as a result of the acceleration of road construction and the increasing congestion of the road network (Yunita & Rifai, 2019); (Calvert & Snelder, 2018); (Nurinda, Priyanto, & Malkamah, 2019); (Singh, Barhmaiah, Kodavanji, & Santhakumar, 2020); (Han, Wang, & Chen, 2022).…”
Section: Introductionmentioning
confidence: 99%